2018
DOI: 10.13189/mst.2018.050201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Wood Particles Reinforced Polymer Composites

Abstract: Natural fiber composites are more attractive due to their high specific strength and lightweight. The focus in this work has been to study the influence of wood fibres on the mechanical properties of the polymer composites manufactured by extrusion and injection moulding process. Tensile and flexural tests were conducted to evaluate the tensile and flexural properties of the compounded composites. The interfacial properties, internal cracks are evaluated by using Scanning Electron Microscope. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Overall, the mechanical properties of the starting WPC (WPC-0) are very good, when compared with earlier studies [ 2 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], as shown in Figure 10 . Even after nine recycles, WPC-9 strength is higher than other WPCs found in the literature [ 24 , 25 , 27 , 30 ].…”
Section: Resultssupporting
confidence: 57%
“…Overall, the mechanical properties of the starting WPC (WPC-0) are very good, when compared with earlier studies [ 2 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], as shown in Figure 10 . Even after nine recycles, WPC-9 strength is higher than other WPCs found in the literature [ 24 , 25 , 27 , 30 ].…”
Section: Resultssupporting
confidence: 57%